Filamentous phage replication initiator protein gpII forms a covalent complex with the 5' end of the nick it introduced. - Asano, S (1999)
Rolling circle type DNA replication is initiated by introduction of a nick in the leading strand of the origin by the initiator protein, which in most cases binds covalently to the 5' end of the nick. In filamentous phage, however, such a covalent complex has not been detected. Using a suitable substrate and short reaction time, we show that filamentous phage initiator gpII forms a covalent complex with nicked DNA, which rapidly dissociates unless gpII is inactivated. A peptide-DNA complex was isolated from trypsin digest of the complex by ion-exchange column chromatography and gel filtration, and its peptide sequence was determined. The result indicated that gpII was linked to DNA by the tyrosine residue at position 197 from the N-terminus. The mutant protein in which this tyrosine was replaced by phenylalanine did not show any detectable activity to complement gene II amber mutant phage in vivo. In vitro, the mutant protein recognized the origin and bent DNA as well as the wild-type does, but failed to introduce a nick and to relax the superhelicity of cognate DNA.